Manajemen Kepala Sekolah dalam Mengembangkan Sekolah Berbasis Teknologi (Studi Di SMP Negeri 1 Hamparan Perak) - Sari, Indri; Elfrianto, Elfrianto; Amini, Amini (UMSU, 2025)
The purpose of this research is to find out how school principals plan, organize, implement and supervise technology-based school development. This research was conducted at SMP Negeri 1 Hamparan Perak. This research method is qualitative research, the subjects of this research consist of the Principal of SMP Negeri 1 Hamparan Perak, Deputy Principal, Teachers and Students. Data collection techniques use interviews, documentation and observation. Data analysis techniques use data collection, data presentation, data reduction and conclusion drawing. The results of this research are:1) The principal's planning for technology-based school development is good, where the principal prepares his work plan for using technology at SMPN 1 Hamparan Perak, and emphasizes teachers to use technology both in school promotions and learning activities at school. 2) The principal organizes technology-based school development well where teachers understand the job description according to the specified tasks and master plan. Then the teacher holds firm in carrying out the school's vision and mission. 3) Implementation in creating a technology-based school at SMP Negeri 1 Hamparan Perak is good where technology supporting facilities already exist, teachers are emphasized to be sensitive to current developments, there is a website, social media at SMP Negeri 1 Hamparan Perak but there are still other obstacles such as inadequate learning facilities. incomplete to support the implementation of technology-based learning. 4) The Principal Supervises Technology-Based School Development through monitoring the role of the deputy principal to evaluate all ongoing activities, the principal carries out personal and group evaluations through teacher meetings. Even though it is running well, many obstacles arise due to the principal's lack of communication.